Analisis Keputusan Mahasiswa Memilih International Class UIN SUSKA Riau Sebagai Tempat Melanjutkan Pendidikan - Diana Eravia (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
This study aims to analyze the faktors affecting students to choose international classes of UIN SUSKA Riau. The population and sample were all of international class student enrolled in UIN SUSKA Riau totaling 68 people. The data was analyzed using multiple regression analysis. The results showed that the independent variable consisting of the geographical faktor, the reference group, the academic program, promotional activities and educational facilities affect the dependent variable that is the decision of students to choose international classes of UIN Suska Riau. Academic program variables was the most dominant faktor in influencing their choice. Based on these results, it is advisable for the management of the program, especially international class in tafsir hadith departement Faculty of Ushuluddin UIN SUSKA Riau to setting strategy and policy that are better targeted in the future.